The socio-philosophical interpretation of economic destructions - Khaitovna, Bekmurodova Gulshoda (Goodwood Publishing, 2025)
Purpose: This study aims to explore the essence and manifestations of economic destruction as a key form of social destruction, highlighting its interplay with constructive and destructive processes in the global economic sphere. The research emphasizes how globalization accelerates both opportunities for growth and risks of instability. Research methodology: A qualitative descriptive approach is applied, using literature review and conceptual analysis of economic trends, globalization processes, and trade relations. The study also integrates comparative insights from international reports and academic discussions to assess the dual nature of constructiveness and destructiveness in economic life. Results: The findings reveal that globalization has intensified trade and economic relations worldwide, fostering constructive dynamics such as innovation, expanded markets, and technological transfer. At the same time, it has amplified destructive processes, including protectionism, indirect barriers, and price volatility. These opposing tendencies coexist and manifest across all sectors, making economic systems simultaneously more integrated and more vulnerable. Conclusions: The research concludes that constructive and destructive processes are inseparable features of contemporary globalization. While they drive economic interdependence and growth, they also generate systemic risks that require careful governance. Recognizing this duality is essential for sustaining balanced global development. Limitations: The study is primarily conceptual and relies on secondary sources, with limited empirical data to capture region-specific destructive impacts. Contribution: This article contributes to academic debates on globalization by framing economic destruction as both a theoretical and practical challenge, offering a lens to understand its systemic impact on global economic relations.